Fatigue Strength of an Urban Type Midi Bus Vehicle Chassis by Using Fem Analysis and Accelerated Fatigue Life Test - Yay, Kubilay; Ereke, I. Murat; Bilir, Mehmet; Çataltepe, Veysel (SAE International, 2009)
Theoretical and experimental techniques in road data are needed for design of vehicle body and chassis according to nowadays technology concept. In this paper, both theoretical analysis and experimental accelerated techniques are explained considering domestic and export production of Anadolu ISUZU company urban type midi bus vehicle. First of all, the chassis and body (skeleton system) of the midi bus vehicle were modeled in 3D by using Catia program and then finite element model (FEM) of the chassis and the body were created by using Ansys, Workbench program. Static and dynamic loading models obtained from dynamic wheel loads acting on the vehicle were developed. In this model, during the service life of the vehicle under vertical and lateral dynamic loads (straight good road, straight bad road, cornering bad road, and singular obstacle road) arising from the road conditions were taken into account. The loading model basically had two different types of loading case, symmetrical loading case and asymmetrical loading case. After performing FEM analysis, critical areas/regions with high stress and deformation values were obtained. A prototype vehicle was run at IDIADA's (Barcelona/Spain) accelerated fatigue test track with a selected test cycle. The critical stress areas/regions obtained from the results of FEM analysis and results/inspections from accelerated fatigue test track were compared. Required design changes were applied to a second prototype vehicle, and this second prototype vehicle was run on selected Turkish roads in order to obtain road load data. The road load data was recorded by using strain gages on different 12 areas considering maximum stress areas on the chassis both obtained FEM results and accelerated fatigue test track at IDIADA in order to perform accelerated fatigue life test on the hydraulic four-poster test system at ITU Automotive Test Laboratory. During the road data collection, additionally displacement values on the front and on the rear suspension systems were also recorded by LVDT(Linear Variable Differential Transformer) sensors mounted two on the front axle and two on the rear axle. Next step was to collect strain and displacement data on the selected eleven different Turkish road routes, totally 650 km. These road load data were then processed by using nCode-ICE-FLOW 4.0 and LMS TecWare-FALANCS signal processing programs and the damage values of each channel for each different road were obtained. According to these damage values of strain measurements and also S-N diagrams of chassis material displacement signals were processed by rainflow analysis. The test chassis of the vehicle was produced and assembled at ITU's rig test bench with the construction of special jigs and fixtures for mounting the chassis to the test bench. For making the strain-gage measurement on the test chassis, the same points/areas as collecting the road load data on the road tests were used. Displacement signals were also arranged so that their damage values from real road conditions to accelerated fatigue test bench were equivalent. After arranging damages of different road signals according to their magnitudes eight big different damage road signals were selected as a driven matrix for four poster. Only rear axle side of the chassis were subjected to accelerated life test of total 150 hours and finally the results of FEM analysis and the results of the accelerated rig test were compared.